The nature of moral thinking - Snare, Francis (Routledge, 1992)
The Nature of Moral Thinking is an introductory text to the questions of ethics, offering a solid philosophical and historical basis for understanding the central issues. Francis Snare discusses in detail the classical philosophical arguments of Plato and Butler in relation to relativism and subjectivism and treats Marx and Nietzsche in regard to the origins and explanation of morality.